Investigating the effect of khat (catha edulis) on selected obesity markers and pathways in C57BL/6J male mice / Mustafa Ahmed Al-Shagga - Mustafa, Ahmed Al-Shagga (2021)
In East African and South Western Arabian populations, Catha edulis (khat) is believed to suppress appetite and reduce body weight. First, this study conducted a systematic review of the literature on the effects of khat and its active alkaloid cathinone on body weight and appetite regulation. Second, this study investigated the effect of khat and cathinone on selected metabolic and histopathologic parameters and their influence on the expression of obesity-related genes in high-fat diet-induced obese mice. Forty-two male C57BL/6J mice were divided into seven groups (n= 6); normal diet control treated with vehicle (NDC), normal diet treated with 200 mg/kg khat extract (NDK200), high fat diet control treated with vehicle (HFDC), high-fat diet treated with 200 mg/kg khat extract (HFDK200), high-fat diet treated with 400 mg/kg khat extract (HFDK400), high-fat diet treated with 3.2 mg/kg cathinone (HFDCAT) and high-fat diet treated with 15 mg/kg orlistat (HFDO). The assigned diet was followed for 16 weeks, with treatment starting from week 9 onwards. Treatments were carried out once daily by gastric gavage for 8 weeks. The systematic review synthesised 15 studies and found that khat consumption is associated with weight loss, appetite suppression, and relatively low triglyceride levels. Nevertheless, studies on the effect of khat on leptin and insulin levels have yielded mixed results, with no mechanistic studies available on the anti-obesity effect of this plant. In our animal experiment. HFD groups gained significant body weight at week 8 than ND groups (p<0.05). After 8 weeks of khat administration, the weight gains of HFDK400 (3.1 ± 0.6 g), HFDCAT (-0.4 ± 2.2 g), and HFDO (3.5 ± 3.8 g) groups gained less weight than the HFDC (9.6 ± 4.3 g) group. The NDK200-treated mice ate less than the NDC group, but the differences in weight gain were not statistically significant. HFDK200, HFDK400, and HFDCAT had less fatty liver and lee fat body mass (p<0.05) and serum triglycerides (p<0.05) than the HFDC group. A dose-dependent decrease in serum leptin was observed in response to khat administration, and it was statistically significant in HFDK400 treated mice (p<0.01), whereas the HFDCAT group was associated with low insulin (p<0.01), low leptin (p<0.001) and low peptide YY (PYY) (p<0.05) levels than the HFDC group. The adiponectin levels in HFDO (3.13 ± 0.3 ng/ml), HFDK200 (3.14 ± 0.6 ng/ml) and HFDK400 (3.16 ± 0.2 ng/ml) treated groups were significantly (p<0.05) higher than the HFDC (1.20 ± 0.1 ng/ml) group. On the contrary, HFDCAT serum iv interleukin-6 (IL-6) (62.7 ± 10.1 pg/ml), was significantly (p<0.05) lower than HFDC (110.1 ± 16.3 pg/ml), whereas serum resistin in HFDK200 (6.0 ±2.0 ng/ml), HFDK400 (3.8 ± 1.7 ng/ml) and HFDCAT (3.3 ± 1.5 ng/ml) groups showed significantly lower levels (p<0.05) compared to HFDC (12.6 ± 1.4 ng/ml). Bone structural histomorphometric parameters showed significantly higher bone volume density (BV/TV) and less trabecular separation in HFDK200 and HFDCAT than the HFDC group (p<0.05). However, HFDCAT had high osteoblast and osteoclast surfaces compared to both khat extract treated groups. The gene expression findings of adipose tissue showed upregulation of the lipolysis pathway gene: adipose triglyceride lipase (PNPLA-2), which reported 3.3, 13.3, 19.3, and 17.7-fold changes for HFDO, HFDK200, HFDK400 (p<0.05), and HFDCAT, respectively, compared to the HFDC vehicle-treated mice. Hormone-sensitive lipase (LIPE) gene expression showed 4.4, 11.2, 19.9, and 11.1-fold changes upregulation for HFDO, HFDK200, HFDK400 (p<0.05), and HFDCAT, respectively compared to the HFDC group. HFDK400-treated mice were also associated with significant overexpression of insulin receptor (INSR) (3.9-fold change), mechanistic target of rapamycin (mTOR) (6.6-fold change), and Glut4 (3.9-fold change), whereas insulin substrate-1 was upregulated in HFDCAT and HFDK200 (p<0.05) compared to the HFDC group. Adiponectin (ADIPQ) showed 51- and 67-fold changes (p<0.05) for both HFDK200 and HFDK400, respectively. Hypothalamic gene expressions revealed a significant (p<0.05) upregulation of agouti-related peptide (AGRP) and cocaineamphetamine regulated peptide (CARTP) genes in HFDK400 (2.5 and 1.9, respectively) and HFDCAT group (4.5 and 4.3, respectively). HFDK200-treated mice showed a significant (p<0.05) overexpression of hypothalamic IL-6 (3-fold change), while the orlistat-treated group did not show any significant hypothalamic gene changes than the HFDC group. In conclusion, the animal study demonstrated a significant effect of khat 400 mg/kg and cathinone on reducing body weight gain in diet-induced obese mice, and this reduction is superior to orlistat. This study supports systematic review findings and provides novel possible peripheral and central anti-obesity mechanisms of khat and cathinone. Keywords: Khat; Catha edulis; Cathinone; Obese mice; Mechanism of action